(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The present study has been performed to encapsulate naproxen to provide sustained action and to minimize local side effects by avoiding the drug release in the upper gastrointestinal tract. Naproxen was microencapsulated by oil-in-oil emulsification-solvent evaporation technique using Eudragit RSPO. The formulations were prepared by sequential increase in drug loading ranging from 10% to 70%. In-vitro drug release was studied in a paddle type dissolution apparatus (USP type II) for six hours in phosphate buffer having pH 7.4. At 10% and 70% loading the release were 42.89% and 86.33%, respectively. The release mechanisms were explored and explained with zero order, first order, Higuchi and Korsmeyer-Peppas models. The correlation-coefficient values of the trend lines of the graphs showed that the formulations were best fitted with Korsmeyer-Peppas release pattern. Microspheres` surface morphologic study was done by scanning electron microscopy. Drug polymer incompatibility studies were performed by Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR). The absence of endothermic melting peak of naproxen in DSC thermogram revealed that the drug might be dispersed in the polymer as solid solution or in a metastable molecular dispersion. But the chemical integrity of Naproxen was not changed or destroyed within the microsphere which was confirmed by FTIR spectral data. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14573 Dhaka Univ. J. Pharm. Sci. 11(2): 147-155, 2012 (December)